Students' interest and usefulness of fieldwork approaches to history - Salleh, Mohamad Johdi; Mohd Ali, Hairuddin (Universiti Riau Indonesia, 2009)
It is very exciting that history in the Integrated Curriculum for Secondary School (ICSS) has been included as one of the core subjects in the lower and upper secondary levels of Malaysian schools. These subjects are officially included in the time table of the ordinary, religious, science, vocational and technical schools in the country. One of the most important and effective methods introduced in the teaching and learning of history is a fieldwork approaches, particularly a site visit. Since history is a compulsory subject, it is necessary to study and analyse the ICSS history curriculum to see if it really could achieve the objectives of the syllabus, successfully imparting knowledge and develop interest among students in the subject. The study involved about eight hundred students of selected secondary schools in the states of Perak and Terengganu. Instruments used were questionnaire and interview which were conducted with the selected respondents. The analysis of the study were presented in percentage by using six Likert scale responses. The study shows that history fieldwork contain many usefulness such as to develop, spark/ stimulate, motivate, investigate, prove, gain social experience, social skills, build teacher-student relation, teaching-learning method, and fulfil National Curriculum. Moreover, the effective used of history fieldwork can enhance student interest in developing the country towards the advancement of ‘first class mind’ of human capital of Malaysian. It is hoped that the finding will enlighten teachers and students in the learning of history in the ICSS towards achieving the stipulated aspiration, especially 1- Malaysia.